STUDY ON THE MECHANICAL PROPERTIES OF TRUSS LATTICE STRUCTURES BY MJF 3D PRINTING (MT) - WANG XuanYu; LI Nan; WURIKAIXI AiYiTi; JIA Ru (Jixie qiangdu)
Seven truss lattice cells were designed by the combined superposition method, and the specimens with the same porosity of seven lattice structures were prepared by the Multi Jet Fusion（MJF） 3D printing technique. The mechanical properties, deformation modes and energy absorption capacity of different lattice structures were analyzed by uniaxial compression experiments and finite element simulations. It show that all seven structures go through the linear elastic stage, platform stress stage and densification stage during the compression process, and the deformation process of SBO structure with bending as the dominant type is relatively smooth, and its platform stress(σpl=2.76 MPa) and platform strain interval length（23% to 72%） are higher than other lattice structures, and the accumulated energy absorption value reach 702 J/mm~3, showing excellent mechanical properties and energy absorption capacity.